The Lived Experience of Australian Women Living with Breast Cancer: A Meta-Synthesis - Rajagopal, Lalithambigai (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Breast cancer is the second most common cancer among Australian women. In 2019, an estimated 19,000 women in Australia were diagnosed with breast cancer, with around 3,058 women dying from the disease in the same year. Although many qualitative studies published in Australia exist which examine breast cancer from various perspectives, only limited literature is available which addresses Australian women’s lived experience of breast cancer from diagnosis, treatment and beyond. METHOD: Meta-synthesis of qualitative studies. Participants who took part in either semi-structured interviews or surveys with open-ended questions were included. A thematic synthesis analysis approach was used. RESULTS: Five themes and 13 sub themes emerged from the data analysis which illustrated the lived experience of Australian women diagnosed with breast cancer. Emotional burden and women’s response towards their breast cancer diagnosis were key themes. Experience of decision- making , social distress, symptoms beyond changes in their body, fertility considerations and their role as mothers were some of the challenges during their treatment. Women coped and adjusted with these challenges through the support of their family, and healthcare providers. Women developed greater empowerment by making their life choices after treatment. Life choices such as getting into a new relationship was challenging for single women. CONCLUSION: Although most women were emotionally supported following their diagnosis, there are still areas where women could be better supported such as when having to break the news of their breast cancer diagnosis to their children, provision of ongoing emotional support for caregivers of women with breast cancer, providing constant emotional and informational support at the point of diagnosis and during their treatment, tailoring treatments according to different stages of pregnancy, and discussion of fertility treatments in timely manner by healthcare professionals.